SLOVENŠČINA KOT DRUGI IN TUJI JEZIK V IZOBRAŽEVANJU – 3. mednarodna znanstvena konferenca Slavistični znanstveni premisleki - Pulko, Simona; Zemljak Jontes, Melita (Slavia Centralis, 2020)
On November 20, 2019, the Faculty of Arts of the University of Maribor hosted the 3rd International Scientific Conference Slavistični znanstveni premisleki entitled Slovenščina kot drugi in tuji jezik v izobraževanju (Slovene as a Second and Foreign Language to Education). The international scientific conference was organized by the Department of Slavic Languages ​​and Literatures of the Faculty of Arts and the Slavic Society Maribor.